Settling down in time and place? Changing intimacies in mobile young people's migration and life courses - Harris, Anita; Baldassar, Loretta; Robertson, Shanthi (Population space and place, 2020)
Transnational mobility is increasingly presented to middle‐class youth globally as a way to secure economic futures in precarious times by enhancing educational and employment opportunities. However, little is said about the benefits and impacts of mobility for social and intimate life and specifically how it is situated within, disruptive of, or incorporated into young people's ideas about relationships as they navigate uncertain pathways to adulthood. This paper critically reviews and integrates migration and youth studies scholarship to consider how contemporary youth mobility can be understood as disrupting standard migration‐ and life‐course conventions about intimate relationships. It focuses particularly on questions of temporality, proximity and synchronicity or orthodoxies of ‘the right time’ and ‘the right place’ to ‘settle down’, in the construction and maintenance of both intimate connections to people and attachments to places. It explores how contemporary youth mobility can be seen to complicate notions of the appropriate staging and chronology for establishing different relationships. It raises questions about synchronicity, continuity and proximity as conditions of intimacy and considers how mobility potentially disrupts gendered and heteronormative life courses to provide both welcome freedoms and new challenges, as well as the emergence of new processes of transnational intergenerational care circulation.